Self-assembled monolayers of oligophenylenecarboxylic acids on silver formed at the liquid-solid interface - Aitchison, Hannah; Lu, Hao; Hogan, Simon W. L.; Früchtl, Herbert; Cebula, Izabela; Zharnikov, Michael; Buck, Manfred (Langmuir, 2016)
A series of para-oligophenylene mono- and dicarboxylic acids (R-(C6H4)nCOOH, n = 1-3, R = H,COOH) was studied. Adsorbed on Au(111)/mica modified by an underpotential deposited bilayer of Ag, the self-assembled monolayers (SAMs) were analyzed by near-edge X-ray absorption fine structure spectroscopy, X-ray photoelectron spectroscopy, and scanning tunneling microscopy. In all cases SAMs are formed with molecules adopting an upright orientation and anchored to the substrate by a carboxylate. Except benzoic acid, all SAMs could be imaged at molecular resolution, which revealed highly crystalline layers with a dense molecular packing. The structures of the SAMs are described by a rectangular (5 × √3) unit cell for the prevailing phase of the monocarboxylic acids and an oblique (93×133) unit cell for the dicarboxylic acids, thus evidencing a pronounced influence of the second COOH moiety on the SAM structure. Density functional theory calculations suggest that hydrogen bonding between the SAM-terminating COOH moieties accounts for the difference. Contrasting other classes of SAMs, the systems studied here are determined by intermolecular interactions whereas molecule-substrate interactions play a secondary role. Thus, eliminating problems arising from the mismatch between the molecular and the substrate lattices, coordinatively bonded carboxylic acids on silver should provide considerable flexibility in the design of SAM structures.